Peer review: An essential component of scientific publications - Zaman, M Mostafa (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
The peer review is for the improvement of the manuscript. Additionally, it helps the editors make an informed decision about the suitability of the manuscript to be published in their journal. Currently, four types of reviews (double anonymized, single anonymized, open, and transparent peer reviews) are commonly followed. None of these are best for all situations. While the authors write the review, they should use the following sections: overview of the manuscript, major points, minor points, and recommendation to the editor. BSMMU gratefully acknowledges 57 reviewers of 45 articles published in 2023.